Designing a Pervasive Adventure Gamescape: Avoiding the Pitfalls in Creating Augmented LBGs for Playful Learning - Katriina Heljakka; Pirita Ihamäki (My University, 2022)
This article reports on the design and evaluation of player experiences in relation to a location-based game (LBG). LBGs seek to move gamified play into the "real world" of cities, parks, and other locations. These games are played in everyday places, where game information is tied to specific locations (Magerkurth et al, 2005). This connection to real-world physicality makes the game experience multidimensional and fun for players of different ages. Yet, to be able to envision and create an urban gamescape means that a set of criteria must be met. The unique challenge of creating and orchestrating LBG experiences requires a certain sensitivity from its designers to the multiple factors that must be considered. These may include-but are not limited to-factors such as the city's infrastructure, the flows of urban traffic, the maintenance of recreational areas, and human-related factors such as cooperation with the city administration. The game introduced in this article-Sigrid-Secrets-represents an urban game adventure built upon the platform of geocaching. We approach the game with a focus on its potential learning affordances. We ask how the pitfalls in creating opportunities for learning through LBGs could be avoided, especially when designing pedagogic aims into an urban gaming experience fit for school-aged children.